Indigenous ingenuity : a celebration of traditional North American knowledge - Havrelock, Deidre; Kay, Edward (Little, Brown and Company, 2023)
Investigates and celebrates the lives and social contributions of a range of Indigenous inventors and thinkers, working in fields of study like astronomy, medicine, agriculture, and engineering. Explores the notion of traditional knowledge as developed by native North Americans.